2013
DOI: 10.1111/jocn.12208
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the relationship between adequacy of dialysis and quality of life and self‐care agency

Abstract: It was recommended to regularly control the parameters used for the assessment of dialysis adequacy and to evaluate their effects on the quality of life, to determine the most affected quality of life subparameters and to address these problems and solve them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 31 publications
1
17
0
5
Order By: Relevance
“…In addition, the urea reduction ratio (URR) is calculated by using pre‐ and postdialysis urea levels (National Kidney Foundation ). However, evaluating dialysis adequacy is challenging (Kalender & Tosun ). Iliescu et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the urea reduction ratio (URR) is calculated by using pre‐ and postdialysis urea levels (National Kidney Foundation ). However, evaluating dialysis adequacy is challenging (Kalender & Tosun ). Iliescu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies comparing QoL and dialysis adequacy using Kt/V report no association including a study of peritoneal dialysis patients on continuous ambulatory peritoneal dialysis or automated peritoneal dialysis that reported no significant difference between dialysis adequacy and various parameters of physical and mental QoL . In contrast, there are a few studies of the general dialysis population that have shown that QoL may be influenced by dialysis adequacy . Simic‐Ogrizovi and others report that haemodialysis patients managed to maintain all four QoL dimensions unchanged over 6 years, and this was due to the quality of haemodialysis, anaemia treatment and a significant increase in their mean Kt/V which can be used as a measure of dialysis adequacy .…”
Section: Discussionmentioning
confidence: 99%
“…33 In contrast, there are a few studies of the general dialysis population that have shown that QoL may be influenced by dialysis adequacy. 34,35 Simic-Ogrizovi and others report that haemodialysis patients managed to maintain all four QoL dimensions unchanged over 6 years, and this was due to the quality of haemodialysis, anaemia treatment and a significant increase in their mean Kt/V which can be used as a measure of dialysis adequacy. 36 Similarly, Manns and associates 37 in a cross-sectional study with 128 haemodialysis patients (mean age 61.8 years) report that dialysis adequacy is significantly associated with QOL in haemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the current state of medical knowledge, for the patients undergoing hemodialysis 3 times per week, the minimum value of dialysis dose Kt/V should equal to 1.2, although it is recommended to reach the range of 1.3-1.4, which is a prerequisite for beneficial long-term results [19]. Up to date reports point to the existence of limited relationships between the indicators of hemodialysis adequacy and the factors of Quality of Life Scale SF-36 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In a recent study conducted by Kalender and Tosun on 112 patients undergoing hemodialysis [15] statistically significant differences have been observed, although with a relatively weak force, between Kt/V and URR and role limitations due to emotional problems in the SF-36 scale.…”
Section: R P R Pmentioning
confidence: 99%
“…Recent studies in this field are insufficient to determine the relationship between life quality and hemodialysis adequacy [11][12][13][14][15]. The problem, which requires further analysis, is the issue of verification of these relationships and the problem of the relationship between sleep disorders and hemodialysis indicators.…”
mentioning
confidence: 95%